The Effect Of Enalapril Maleat In Ischemia Reperfusion Injury: Possible Role of Membrane Bound Enzymes - (:unkn) unknown (My University, 2001)
The present study evaluates the protective effect of enalapril maleat on myocardial ischemia-reperfusion injury. Membrane bound enzymes; Na(+)K(+)/Mg(2+) ATPase and Ca(2+)/Mg(2+) ATPase are known to regulate the membrane integrity. We hypothesized that if we could protect the cell membrane in ischemia-reperfusion period, we might have a chance to augment contractility. Thirty-two Guinea pig hearts were studied in an isolated Krebs-Henseleit solution-perfused Langendorff cardiac model. In Group 1, control hearts (n = 8) were arrested with St. Thomas Cardioplegic Solution (STHCS) alone. In Group 2 (n = 8), animals were pretreated with oral enalapril maleat (0.2mg/kg/daily) for ten days and arrested with STHCS. In Group 3, (n = 8) the hearts were arrested with enalapril maleat- (1 µmol/L) added STHCS. In Group 4 (n = 8), the hearts were again pretreated with oral enalapril maleat for ten days and then reperfused with enalapril maleat-added Krebs-Henseleit solution. Hearts were subjected to normothermic global ischemia for 90 minutes and then were reperfused at 37 degrees C. The study groups showed better recovery of left ventricular systolic function. In terms of biochemical determinations, best results were achieved at Group 4. The Na(+)K(+) ATPase and Ca(2+) ATPase levels were measured at 466.38 +/- 5.99 to 545.23 +/- 8.79, and 884.69 +/- 9.13 to 1254.34 +/- 1.56, respectively (p < 0.05). Based on these results, it can be concluded that enalapril maleat protects the membrane integrity and thus plays a role in restoring the contractility in ischemia-reperfusion injury. </hea